Implantação do Programa de Residência Médica no município de Angra dos Reis - Coelho, Ivan Batista; Machado, Lilian Gomes; Cabral, Cristiane Coelho; Farias, André Luiz da Silva (Revista Acadêmica GUETO, 2024)
Projeto